2020
DOI: 10.3390/ma13194256
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Cooling Rates on the Microstructure and High-Temperature Mechanical Properties of a Nickel-Based Single Crystal Superalloy

Abstract: The as-cast alloy of nickel-based single-crystal superalloy was used as the research object. After four hours of solution treatment at 1315 °C, four cooling rates (water cooling (WC), air cooling (AC) and furnace cooling (FC1/FC2)) were used to reduce the alloy to room temperature. Four different microstructures of nickel-based superalloy material were prepared. A high-temperature tensile test at 980 °C was carried out to study the influence of various rates on the formation of the material’s microstructure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Thus, the hardness can be improved to a certain extent. In addition, the increased volume fraction of reversed austenite in 3Cu significantly reduced the hardness [ 30 , 31 ], and the combined effect of the two factors reduced the HRC of 3Cu steel compared with that of 1.5Cu steel. At tempering temperatures above 650 °C, the refinement of ε-Cu relative to the grain weakened, along with the reduction in the reversed austenite, balancing each other and making the HRC of the two test steels remain basically the same.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the hardness can be improved to a certain extent. In addition, the increased volume fraction of reversed austenite in 3Cu significantly reduced the hardness [ 30 , 31 ], and the combined effect of the two factors reduced the HRC of 3Cu steel compared with that of 1.5Cu steel. At tempering temperatures above 650 °C, the refinement of ε-Cu relative to the grain weakened, along with the reduction in the reversed austenite, balancing each other and making the HRC of the two test steels remain basically the same.…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al [19] investigated the influence of cooling mode on morphology evolution and γ′ precipitates in NBSC superalloys, observing increased average matrix and precipitation channel widths with decreasing cooling rates. Wang et al [20] scrutinized the impact of varied cooling rates on the microstructure formation of NBSC superalloys. Their results indicated that an escalated cooling rate led to the formation of smaller quantities of the γ′ phase, with air cooling demonstrating optimal uniformity in precipitated γ′ phases and coherence with the γ phase.…”
Section: Introductionmentioning
confidence: 99%
“…The coarsening of the γ′-phase and the formation of a carbide net at the grain boundaries significantly reduced the tensile strength and reduced the toughness by almost 50%. In their work, Wang et al [ 25 ] described the effect of cooling rate (0.15 °C/s, 0.60 °C/s, 72 °C/s, and 138 °C/s) on the microstructure and high-temperature mechanical properties of the experimental monocrystalline superalloys. They found that as the cooling rate increased, the γ′-phase nucleation rate increased, resulting in an increased volume of this phase.…”
Section: Introductionmentioning
confidence: 99%